CRC handbook of terpenoids: triterpenoids volume I: acyclic, monocyclic, bicyclic, tricyclic, and tetracyclic terpenoids - Dev, S.; Nagasampagi, B.A. (CRC Press, Inc., 2018)
This Handbook, pinpoints salient features of known information about Terpenoids in a readily accessible and readable format. Terpenoids have singularly enriched organic chemistry by its variety of structural types, by its wealth of“unexpected” reactions, rearrangements and spectral features, and by offering exciting targets for synthesis. Much imaginative experimental work has been invested in exploring their natural pathways. Recent years have revealed an increasingly important biological and ecological role for several of its members.